2017
DOI: 10.4236/wjet.2017.52b001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Fertilization Treatments on Soil, Leaf Nutrient and Fruit Quality of Citrus grandis var. longanyou

Abstract: The five-year-old "Longanyou" trees were used as the experimental material to study the effects of different fertilization treatments. The nutrient contents in soil and leaves, fruit yield and quality were determined, and then the correlations were analyzed. The results showed that: 1) The soil nutrient contents of 0-20 cm depth were more than the 20-40 cm, and the trends of nutrient contents of the 0-20 cm soil layers were as follows: treatment 2 (T2) > treatment 3 (T3) > treatment 4 (T4) > treatment 1(T1) > … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 3 publications
3
2
0
1
Order By: Relevance
“…e study demonstrated that the leaf P, K, and Mg concentrations were positively correlated with TSS content and yield but negatively correlated with acidity (Figure 2), which agrees with the results of Li et al [58] who reported that there was a positive correlation between the leaf nutrients (P, K, and Mg) and TSS content of citrus fruits or yield. Similarly, we found that most of the nutrients in citrus fruits were negatively correlated with the acidity of fruits and positively correlated with the TSS content and fruit yield (Figure 3).…”
Section: Discussionsupporting
confidence: 89%
“…e study demonstrated that the leaf P, K, and Mg concentrations were positively correlated with TSS content and yield but negatively correlated with acidity (Figure 2), which agrees with the results of Li et al [58] who reported that there was a positive correlation between the leaf nutrients (P, K, and Mg) and TSS content of citrus fruits or yield. Similarly, we found that most of the nutrients in citrus fruits were negatively correlated with the acidity of fruits and positively correlated with the TSS content and fruit yield (Figure 3).…”
Section: Discussionsupporting
confidence: 89%
“…According to Xiao et al [19], organic fertilizer combined with compound fertilizer improved soil quality, whereas the utilization of compound fertilizer worsened soil quality and made the soil acidize; this result was similar to that of Song et al [20] and Pachuau et al [23]. Qiu et al [15] reported that chemical fertilizer combined with biofertilizer application significantly promoted root growth, improved the rate of nutrient distribution in citrus, and improved the external and internal qualities of tarocco blood orange; this result was similar to those of previous study of citrus [24][25][26]. According to Pei et al [7], organic fertilizer is an alternative to chemical fertilizer with no loss in yield and fruit quality for citrus.…”
Section: Introductionsupporting
confidence: 89%
“…This has led to deterioration of soil properties and ecological environment. However, a combination of chemical and organic fertilizer is not only beneficial in improving the properties and environment of soils, but also promotes crop yield and quality [19][20][21][22][23][24][25][26][27][28][29][30]. Here, our work confirmed that CFOF was helpful in increasing citrus yield and improving soil properties.…”
Section: Discussionsupporting
confidence: 73%
“…Beside the genetic character, the levels of nutrients absorbed in the leaves also generally depend on the fertility status of its media. According to Li et al [13], the contents of B, Zn and Fe in leaves of Citrus grandis var. Longanyou were significantly correlated with soil nutrient.…”
Section: Leaf Nutrient Statusmentioning
confidence: 99%